Differences In Isotonic Beverages Compared to Mineral Water on Blood Pressure, Heart Rate and Sodium in Students of The Faculty of Nursing Universitas Prima Indonesia Underwriting Circuit Training - Johanna Fransiska Wijaya; Djamin Katarino; Corry Ida Hinaya Zaluku (International Journal of Health and Pharmaceutical (IJHP), 2023)
Circuit training is a training system that can simultaneously improve the overall fitness of the body, namely the elements of power, endurance, strength, agility, speed, and other components of physical condition. This research is an experimental research Pretest-Posttest Control Group Design. The sample in this study were students of the Faculty of Nursing at Prima Indonesia University. The sample numbered 20 people, divided into 2 groups and none of them withdrew. Data processing using the SPSS program version 23. Research time was Wednesday, 14 August 2019 to Monday, 19 August 2019. The results showed that the participants who were given isotonic fluids experienced a significant decrease in systolic blood pressure (p<0.05) and heart rate (p<0.05) on the first and second days due to body adaptation, while on the third to fifth day the decrease did not occur. significant (p>0.05). There was a significant increase in systolic blood pressure (p<0.05) and heart rate (p<0.05) in participants who were given mineral water. Giving isotonic fluids or minerals does not affect diastolic blood pressure. However, there was an increase in blood sodium levels (p<0.05) in participants who were given isotonic fluids, while in participants who were given mineral water there was a decrease in blood sodium levels (p<0.05).